PENGALAMAN KEBAHAGIAAN KARYAWAN GEN Z: PERSPEKTIF FENOMENOLOGI PADA PEKERJAAN PERTAMA - Putu Irma Yunita,; Kadek Reno Kusuma,; I Putu Dharmawan Pradhana,; I Putu Yoga Purnama Wijaya, (Juremi: Jurnal Riset Ekonomi, 2024)
Currently, Indonesia is entering the era of society 5.0, where this era is not much different from the era of society 4.0. Indonesia is considered late in entering this era. There are several factors that influence Indonesia to be a bit late in entering this era. one of the factors is low Human Resources (HR). This year Generation Z has started to enter the world of work, Gen Z claims to be the generation that works the hardest, but because they value flexibility as a very important principle, Gen Z will not be willing to be forced to work when they don't want to work. However, not all workplaces have the criteria desired by generation Z, so from this phenomenon it can be questioned whether generation Z is happy in their first job. This research uses qualitative methods by interviewing 7 informants. The results of this research are that generation Z workers, especially in their first job, experience less happiness, which causes their work performance to decline. One of the factors that makes their work performance decrease or they are less happy is work that is not in accordance with their wishes or passion, they do not have work experience or experience and a work environment that blinds their work performance